2000
DOI: 10.1677/joe.0.1660235
|View full text |Cite
|
Sign up to set email alerts
|

Role of genetic factors in the pathogenesis of osteoporosis

Abstract: Osteoporosis is a common disease with a strong genetic component characterised by low bone mass, microarchitectural deterioration of bone tissue and an increased risk of fracture. Twin and family studies have shown that genetic factors play an important role in regulating bone mineral density and other determinants of osteoporotic fracture risk, such as ultrasound properties of bone, skeletal geometry and bone turnover. Osteoporosis is a polygenic disorder, determined by the effects of several genes, each with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
126
0
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(133 citation statements)
references
References 98 publications
(51 reference statements)
1
126
0
6
Order By: Relevance
“…Although evidence shows such an association, it has been shown to be dependent on the site of measurement, age, and ethnicity of the study population. Thus, no consensus has been made on the role of ERa polymorphism on female BMD (6). ERa polymorphism may be of interest in men as well in view of the evidence supporting the importance of estrogen on the male skeleton (3), but only a few reports have studied its role in association with male BMD (18,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although evidence shows such an association, it has been shown to be dependent on the site of measurement, age, and ethnicity of the study population. Thus, no consensus has been made on the role of ERa polymorphism on female BMD (6). ERa polymorphism may be of interest in men as well in view of the evidence supporting the importance of estrogen on the male skeleton (3), but only a few reports have studied its role in association with male BMD (18,35).…”
Section: Discussionmentioning
confidence: 99%
“…Although environmental factors such as nutrition and physical activity may affect the peak bone mass, genetic factors are the deciding determinants (5). Several genes, such as the vitamin D receptor, estrogen receptor a (ERa), type 1 collagen, and transforming growth factor-b genes, have been studied for an association between their genetic polymorphisms and bone mass (6). In most of these studies, however, the study populations have been postmenopausal women, in whom accretion of bone mass has ceased and bone loss has begun.…”
Section: Introductionmentioning
confidence: 99%
“…The BMD, a good scale to predict the risk of subsequent fractures, is regulated by both polygenes and environmental factors. Although both twin and family studies have shown that 50-80% of age-related variance of BMD are genetically determined (Eisman 1999;Stewart and Ralston 2000), genetic susceptibility to osteoporosis has not fully been understood. Previous studies demonstrated that BMD is associated with several genes/proteins.…”
Section: Introductionmentioning
confidence: 99%
“…1 Positive family history is one of the major risk factors for osteoporosis, and epidemiological studies indicate that genetic factors contribute substantially to susceptibility to osteoporosis. 2 In 1998 we first reported a whole-genome scan of osteoporosis-related traits, based on the analysis of a small sample of extended Caucasian pedigrees of Canadian origin that had been selected through a proband with low bone mineral density (BMD). 3 Our study focused on quantitative trait linkage analysis of lumbar spine (LS) and femoral neck (FN) BMD and identified three regions with lod-scores X2.2 on chromosomes 1p, 2p, and 4q.…”
Section: Introductionmentioning
confidence: 99%